Prevalence of post-traumatic stress disorder and associated factors among Koshe landslide survivors, Addis Ababa, Ethiopia: a community-based, cross-sectional study. Issue 6 (29th June 2019) - Asnakew, Sintayehu; Shumet, Shegaye; Ginbare, Worknesh; Legas, Getasew; Haile, Kalkidan
Abstract : Objectives: To assess the prevalence of post-traumatic stress disorder (PTSD) and associated factors among the survivors of Koshe landslide, Addis Ababa, Ethiopia, 2018. Design: Community-based cross-sectional design. Setting: Koshe landslide, Addis Ababa, Ethiopia. Participants: We recruited 830 participants for interviews using the simple random sampling technique. Measurement: We collected data by face-to-face interviews. The civilian version of the PTSD checklist was used to measure the symptoms of the disorder. The Perceived Stress Scale and the Oslo-3 social support instruments were used to assess the factors. Coded variables were entered into Epi data V.4.2 and exported to SPSS V.24 for analysis. Bivariate and multivariate logistic regressions with OR and 95% CI were employed. Result: A total of 830 participants were interviewed, with a response rate of 98.2%. The prevalence of PTSD was 37.3% with 95% CI 34.1 to 40.8. In the multivariate logistic regression, female sex (adjusted odds ratio (AOR)=1.74, 95% CI 1.21 to 2.50), divorce (AOR=2.08, 95% CI 1.26 to 3.43), sustained physical injury (AOR=8.28, 95% CI 5.04 to 13.61), history of mental illness (AOR=5.55, 95% CI 2.30 to 13.36), family history of mental illness (AOR=2.82, 95% CI 1.48 to 5.37), poor social support (AOR=3.64, 95% CI 1.99 to 6.69) and high perceived stress (AOR=3.08, 95% CI 1.43 to 6.64) were associated with PTSD. Conclusion and recommendations: The prevalence of PTSD among the survivors of Koshe landslide was high. We recommend that an early PTSD-focused regular screening be carried out by trained health professionals; linkage with mental health service providers also needs to be considered.